Allylation Reactions of N,O-Heterocycles - Bates, Roderick W.; Tang, Chi H.; Tan, Yuting; Buang, Siti Nurhayati binte (Synlett, 2012)
Iminium ions generated from isoxazolidines and tetrahydro-1,2-oxazines undergo allylation under Sakurai conditions. Allylated isoxazolidines are formed predominantly as the trans isomer, while oxazines are formed exclusively as the cis isomer.
Keywords: heterocycles; allylation; stereoselectivity